Analysis of current epilepsy treatment guidelines - Kulczyński, Marcin; Marciniec, Michał; Sapko, Klaudia; Ficek, Remigiusz (Journal of Education, Health and Sport, 2019)
Introduction: In 2017, the International League Against Epilepsy (ILAE) published a new classification of seizures. The purpose of this publication is to analyze the use of antiepileptic drugs in epilepsy therapy depending on the types of seizures classified according to ILAE 2017.State of the art: The new basic classification emphasizes mainly the location, where seizures begin in the brain, as the most important criterion to classify epileptic seizures. In focal onset seizures, 1st line of treatment in children is oxcarbazepine, while carbamazepine, levetiracetam, phenytoin and zonisamide is 1st choice in younger adults and gabapentin and lamotrigine in elderly patients. In younger adults valproic acid can be considered as second line treatment. In generalized tonic and atonic seizures carbamazepine, phenobarbital, phenytoin, topiramate, oxcarbazepine and valproic acid can be used both in children and adults. Safe and effective drugs in myoclonic and myoclonic-atonic seizures in all age groups are topiramate and valproic acid. In absence seizures, 1st line treatment in children is ethosuximide (used exclusively in this seizures type) and valproic acid, while carbamazepine, lamotrigine, oxcarbazepine, phenobarbital, phenytoin, topiramate, valproic acid, gabapentin, levetiracetam and vigabatrin are commonly used in adult patients. Non-pharmacological approaches, used in refractory epilepsy, include: surgical resection of the seizure focus, the ketogenic diet, vagus nerve stimulation and responsive neurostimulation.Summary: The new ILAE classification corresponds well with the old guidelines well, which leads to simplifying and spreading the knowledge about epileptic seizures treatment.